Analisis Kebergunaan Website Dinas Pertanian Kabupaten Lombok Tengah Menggunakan Metode WEBUSE: Penelitian - Silvia Eka Dewi; Saikin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to evaluate the usability level of the official website of the Central Lombok Agriculture Office as a digital public service platform. The evaluation was conducted due to the absence of prior assessments regarding the website’s effectiveness and its ability to meet user needs. The Website Usability Evaluation (WEBUSE) method was applied, covering four main dimensions: Content, Accessibility, Interaction, and Reliability. Data were collected through observation, interviews, and a Likert-scale questionnaire administered to 40 respondents. The results show that all dimensions obtained a score of 0.20, categorized as Poor, indicating that the quality of information, ease of access, user interaction, and system reliability remain low. These findings highlight the need for improvements in content quality, navigation structure, interactive features, and system performance to enhance the website’s overall usability. This study is expected to serve as a reference for the local government in improving digital public service platforms.